CURRENTS OF CULTURE: RIDERS TO THE SEA AS A BLUE HUMANITIES TEXT - Kurian, Viju; Gopalakrishnan, Kavitha (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This article reinterprets J.M. Synge’s Riders to the Sea through the framework of Blue Humanities, focusing on portraying the sea as a force central to modern tragedy. The play depicts the sea as a natural element and an overwhelming, indifferent power, shaping the tragic fate of coastal lives. The sea narrative is explored in its dual role as a sustaining and threatening force, reflecting the deep cultural ties between the islanders and the ocean. Finally, the analysis turns to the theme of the blue economy, examining how the characters’ dependence on the sea for survival intertwines with their profound losses. By situating Riders to the Sea within these contexts, the article underscores the timeless significance of maritime themes in understanding human suffering and resilience.